Entrepreneurship : a small business approach - Bamford, Charles E.; Bruton, Garry D. (McGraw-Hill, 2011)
Taking a problem-based learning approach that works through real problems faced by entrepreneurs and small business owners, this title puts the student in the roles of financial analyst, marketer, and business owner to find solutions. It provides students with the necessary foundation to design, start, and manage a small business